Tendering Management and Performance of State Agencies under the Ministry of Agriculture and Livestock Development, Kenya - Nzioka, Esther; Odari, Sammy; Ndeto, Charles (International Journal of Supply Chain and Logistics, 2025)
Purpose: The general objective of the study was to determine the relationship between tendering management and the performance of state agencies under the Ministry of Agriculture and Livestock Development, Kenya. The study was anchored on game theory. Methodology: The study adopted explanatory research design. Positivist research philosophy was adopted. The target population was 192 management team in 32 state agencies under the Ministry of Agriculture and Livestock Development. The study adopted a census approach and hence the whole population was included in the study. The study used primary as well as secondary data. The questionnaires generated qualitative and quantitative data. Thematic analysis was used to analyze qualitative data and the results were presented in a narrative form. Descriptive and inferential statistics were used in analyzing quantitative data with the assistance of statistical software. Findings: The study found that tendering management has a positive and significant relationship on performance of state agencies under the Ministry of Agriculture and Livestock Development, Kenya. Unique Contribution to Theory, Policy, and Practice: From the findings, the study recommends management of State agencies under the Ministry of Agriculture and Livestock Development, Kenya should adopt a robust e-procurement system complemented by continuous capacity-building initiatives for procurement staff. The study advances theory by showing e-procurement’s role in enhancing efficiency and transparency, informs policy by supporting stronger frameworks and staff capacity-building, and guides practice by urging state agencies to adopt robust digital procurement systems.